(untitled) (International Journal of Environmental Sciences, 2025)
The purpose of this research study is to understand the effective factors from consumer perspective, encourage fluctuation in brand equity Titan of Tata Group especially in watch industry in India. The factors tested in this research study are brand differentiation, brand relevance, brand esteem, brand knowledge and brand sustainability. A convenient sampling technique was applied for collecting the data from 350 respondents through google form, email and WhatsApp. The reliability and validity of the factors driving fluctuation in brand equity of Titan were tested by correlation analysis and multiple regression analysis through SPSS software. The findings of this research study are positive and strong relationship between all these factors and brand equity in case of Titan brand. This study is helpful in managing brand equity as which factor having a strong impact and low impact on brand equity.